Increased functional potency of multi-edited CAR-T cells manufactured by a non-viral transfection system - Aine O’Sullivan; Sarah Case; Aisling McCrudden; Emer Hackett; Louise Gallagher; Darren Martin; Gillian P. Johnson; Kirti Mahadik; Thomas Kienzle; Jude Kevin Lim; Aya Nashat; Kartik Srinivasan; et al. (Molecular Therapy: Methods & Clinical Development)
Chimeric antigen receptor (CAR)-T cell therapy represents a breakthrough for the treatment of hematological malignancies. However, to treat solid tumors and certain hematologic cancers, next-generation CAR-T cells require further genetic modifications to overcome some of the current limitations. Improving manufacturing processes to preserve cell health and function of edited T cells is equally critical. Here, we report that Solupore, a Good Manufacturing Practice-aligned, non-viral physicochemical transfection system, can be used to manufacture multi-edited CAR-T cells using CRISPR-Cas9 ribonucleoproteins while maintaining robust cell functionality. When compared to electroporation, an industry standard, T cells that were triple edited using Solupore had reduced levels of apoptosis and maintained similar proportions of stem cell memory T cells with higher oxidative phosphorylation levels. Following lentiviral transduction with a CD19 CAR, and subsequent cryopreservation, triple-edited CAR-T cells manufactured using Solupore demonstrated improved immunological synapse strength to target CD19+ Raji cells and enhanced cellular cytotoxicity compared with electroporated CAR-T cells. In an in vivo mouse model (NSG), Solupore triple-edited CAR-T cells enhanced tumor growth inhibition by more than 30-fold compared to electroporated cells.